A Quasistraight Line Routing Protocol for Square Grid-Based Wireless Sensor Networks. (11th May 2022) - Ajij, Md.; Pratihar, Sanjoy; Luhach, Ashish Kumar; Roy, Diptendu Sinha
Abstract : Sensor nodes in a wireless sensor network (WSN) are both energy-constrained and vulnerable to faults and disasters. Communication between the sensor nodes is generally hop-by-hop, and the nodes are distributed throughout the area to be covered. Broadcast-based routing protocols are not preferable in sensor networks since broadcasting is considered costly in terms of battery power consumption. In this paper, a digital quasistraight line segment- (DQSS-) based approach is employed for the detection of quasistraight line segments, i.e., for quasistraight path finding between WSN sensors arranged in a square grid. Comparative results show that the method is comparable with the best-known straight line finding algorithm in terms of path lengths and computation time. Moreover, the proposed method is capable of avoiding dead nodes by updating DQSS parameters dynamically during path finding. Hence, the proposed method is promising to be used in WSN square grids as a quasistraight line routing protocol.